2021
DOI: 10.21037/jtd-20-2356
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of volume changes in the descending aorta after frozen elephant trunk procedure using the Thoraflex hybrid prosthesis for type A aortic dissection

Abstract: Background: Frozen elephant trunk (FET) is an established approach to reduce late complications of type A aortic dissection (AADA) by diminishing false lumen perfusion. Currently, surface size of aortic lumina are evaluated using Computed tomography (CT). However, this 2D method is prone to error as it evaluates dissection progression slice by slice. Volume measurement on the other hand can overcome this limitation and deliver better insights in aortic remodeling. Therefore, the aim was to quantify volume chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…These long-term outcomes seem to be congruent a previous 2018 study, where chronic dissection patients showed significant TL expansion (15 ± 17 mm to 28 ± 2 mm) (p = 0.001) and FL diameter drop (40 ± 11 mm to 32 ± 17 mm) (p = 0.026) 2 years following the procedure (15). Additionally, Usai et al (14) confirmed that in their study almost all Thoraflex Hybrid TM patients had significant TL expansion and reported only 1 patient required reintervention, due to a FL aneurysm. Furthermore, the authors also noted that the most significant growth in the surface TL measurement was at the level of the diaphragm (p = 0.00193) (14).…”
Section: Aortic Remodelingsupporting
confidence: 89%
“…These long-term outcomes seem to be congruent a previous 2018 study, where chronic dissection patients showed significant TL expansion (15 ± 17 mm to 28 ± 2 mm) (p = 0.001) and FL diameter drop (40 ± 11 mm to 32 ± 17 mm) (p = 0.026) 2 years following the procedure (15). Additionally, Usai et al (14) confirmed that in their study almost all Thoraflex Hybrid TM patients had significant TL expansion and reported only 1 patient required reintervention, due to a FL aneurysm. Furthermore, the authors also noted that the most significant growth in the surface TL measurement was at the level of the diaphragm (p = 0.00193) (14).…”
Section: Aortic Remodelingsupporting
confidence: 89%
“…Our results, however, contradict those of Weiss et al which did not find, significant change in both diameters [ 1 ]. With regards to true lumen expansion, our results are in agreement of Marco et al [ 7 ] who studied the lumens at the level of celiac axis and pulmonary bifurcation, however, in our study, at the level of the pulmonary bifurcation the distal part of the stent was almost always present and not the actual unstented part of the true lumen. Similarly, Song et al [ 8 ] showed true lumen expansion at the level of the diaphragm and the celiac axis.…”
Section: Discussionsupporting
confidence: 92%
“…This could be related to remodelling of the aorta after the Thoraflex hybrid prosthesis implantation in the acute dissection group. This is supported by recently published data demonstrating significant volume changes in true lumen in the descending aorta after FET procedure using the Thoraflex hybrid prosthesis (11). We were able to show that use of the FET procedure for acute aortic dissection leads to a statistically measurable increase in the true lumen volume from the left subclavian artery to the celiac trunk at the short-term follow-up examination (upon discharge) (11).…”
Section: Discussionsupporting
confidence: 84%
“…The FET technique has been described early (11). A prophylactic antibiotic (Cefazolin, 2 g) was routinely administered to all patients before and after the procedure (for 24 hours).…”
Section: The Fet Techniquementioning
confidence: 99%
See 1 more Smart Citation